Inside, outside, upside down - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012. (New York, Random House, 1968)
A simple tale, using a limited vocabulary for young readers, of how little bear travels to town in a cardboard box.
"BE 4"--Spine.
120L
Decoding demand: 70 (high) Semantic demand: 14 (very low) Syntactic demand: 11 (very low) Structure demand: 13 (very low)
edited hb 2015-06-16
Keywords: Bears -- Fiction; Berenstain Bears (Fictitious characters) -- Fiction; Bears; Bears; Berenstain Bears (Fictitious characters); Berenstain Bears (Fictitious characters); Fiction; Fiction